TERRY TOWEL IN BANGLADESH - Al Faruque, Abdullah; Kader, Shahidul; Patwary, Sarif Ullah; Mishuk, Aminul Islam; Anwarul Azim, Abu Yousuf Mohammad; Khatun, Sarmin (European Scientific Journal, ESJ, 2015)
Terry towel is one of the fast growing and challenging sub sector of the textile sector of Bangladesh. Bath robes, hand towel, kitchen towel etc. are the products from terry in one word. Demand of these products is increasing very fast globally and also significantly day by day in the local market. Consumers pay on an average $7 for bath towel and their households in America. In last decades, the importance of this sector has been increased enormously with the incremental global demand. As Bangladesh is one of the major terry products exporting country among the terry manufacturing countries of the world. This report covers a details study about terry towel including manufacturing process, classsification and physical properties export import volume of terry towel.